2015
DOI: 10.1523/jneurosci.4137-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Modulations in Oscillatory Frequency and Coupling in Globus Pallidus with Increasing Parkinsonian Severity

Abstract: While beta oscillations often occur within the parkinsonian basal ganglia, how these oscillations emerge from a naive state and change with disease severity is not clear. To address this question, a progressive, nonhuman primate model of Parkinson's disease was developed using staged injections of MPTP. Within each parkinsonian state (naive, mild, moderate, and severe), spontaneous local field potentials were recorded throughout the sensorimotor globus pallidus. In the naive state, beta oscillations (11-32 Hz)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
67
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 61 publications
12
67
1
Order By: Relevance
“…In several rodent models of PD, dopamine depletion does result in an increase in the amplitude of beta oscillations in several structures in the basal ganglia-thalamocortical loop (Costa et al, 2006; Mallet et al, 2008). However, other studies using progressive model of parkinsonism in rodents and non-human primates showed equivocal changes in beta oscillations (Connolly et al, 2015; Devergnas et al, 2014; Leblois et al, 2007; Leventhal et al, 2012). Although the amplitude of beta oscillations in the LFP power spectrum is reduced by successful therapy in humans, this reduction should not necessarily be interpreted as returning the STN to its “normal” state.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In several rodent models of PD, dopamine depletion does result in an increase in the amplitude of beta oscillations in several structures in the basal ganglia-thalamocortical loop (Costa et al, 2006; Mallet et al, 2008). However, other studies using progressive model of parkinsonism in rodents and non-human primates showed equivocal changes in beta oscillations (Connolly et al, 2015; Devergnas et al, 2014; Leblois et al, 2007; Leventhal et al, 2012). Although the amplitude of beta oscillations in the LFP power spectrum is reduced by successful therapy in humans, this reduction should not necessarily be interpreted as returning the STN to its “normal” state.…”
Section: Discussionmentioning
confidence: 89%
“…However, one of these studies also showed that a discrete peak was found consistently in the 11–30 Hz range in both disease groups, and that synchronization of neuronal firing with LFP oscillations is a more prominent feature in PD than in dystonia (Weinberger et al, 2012). In a recent study of MPTP-induced parkinsonism in nonhuman primates, resting state beta oscillations were present in the naïve pallidum, and after induction of parkinsonism, beta band power was not correlated with disease severity (Connolly et al, 2015). Future studies comparing LFP oscillations and spike-field relationships in different movement disorders may clarify the disease specificity of biomarkers in the pallidum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oscillatory synchronization in the 8-30 Hz (beta) band has been observed in the STN, GPi and primary motor cortex in humans undergoing DBS surgery (Kuhn et al , 2009), in the MPTP non-human primate model of Parkinson's disease (Devergnas et al , 2014), and in rats treated with 6-hydroxydopamine (Gradinaru et al , 2009). Other studies however, have questioned a causative role of beta band oscillations in the pathogenesis of Parkinson's disease finding that such oscillations occur in the naïve state (Connolly et al, 2015b; Courtemanche et al, 2003; Leventhal et al, 2012; Murthy and Fetz, 1992), that motor signs may precede the occurrence of oscillatory activity in the GPi and STN (Leblois et al , 2007), and that these oscillations are not found in all Parkinson's disease patients (Rosa et al , 2011). Thus, the precise nature of changes in neuronal activity within the basal ganglia and their role in the development of Parkinson's disease motor signs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Effective DBS also suppresses the exaggerated low-frequency brain oscillations in both rodent and NHP models of PD [94]. In fact, the extent of the low-frequency oscillations correlates with disease severity in the MPTP NHP PD model [95]. Although the results from studying DBS in preclinical disease models are overall consistent with the clinical findings, they also fall short of distinguishing whether the abnormal low-frequency brain activity is a cause or only a symptom of the associated motor dysfunction.…”
Section: Accepted Manuscriptmentioning
confidence: 85%